(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article investigates psycholinguistic constraints and translation solutions in children’s literature with a special focus on balancing simplification and preserving the cognitive potential of literary texts for young target readers. The study examines children’s age-related perception of texts, the role of emotionality, playfulness of language, and cognitive development in the translation process. The paper analyzes the main translation strategies applied in adapting children’s literature, including explicitation, simplification, compensation, and cultural adaptation. The research material includes English children’s literary works and their translations. The study demonstrates that excessive simplification may reduce the educational and developmental functions of literature, whereas an adequate translation contributes to imagination, linguistic competence, and cognitive growth.